Analysis of fatigue and tremor during sustained maximal grip contractions using Hilbert-Huang Transformation - Li, Ke; Hogrel, Jean-Yves; Duchêne, Jacques; Hewson, David J. (Medical engineering & physics, 2012)
The objective of this study was to evaluate muscle fatigue and tremor during a Sustained Maximal Grip Contraction (SMGC) using the Hilbert-Huang Transformation (HHT). Thirty-nine healthy subjects volunteered for the study and performed a 25-s SMGC. Fatigue parameters such as the relative force output (RFO) were calculated from the residual of SMGC after applying Empirical Mode Decomposition (EMD). Using the energy spectrum of the Intrinsic Mode Functions (IMF) obtained using HHT, isometric force tremor was identified from the 4 to 12Hz region in IMF3 and IMF4. Data were analysed for five consecutive 5-s epochs to identify changes in fatigue and tremor over time. The HHT method was able to identify a greater resistance to fatigue in women compared to men (p≤0.05) and in non-dominant hands compared to dominant hands (p≤0.05). Consistent with the results for fatigue, women had less tremor than men (p≤0.05), while non-dominant hands trembled less than did dominant hands (p≤0.05). Higher levels of tremor were observed for non-fatigue-resistant subjects for both 10–15s and 15–20s epochs (p≤0.05). The HHT is an appropriate method to identify both fatigue and tremor during SMGC. It would be of interest to apply this method to the study the elderly or patients with neuromuscular disorders.